Utilización de las bacterias ácido lácticas provenientes del mucilago de cacao (theobroma cacao l.) nacional para mejorar el sabor y textura del queso mozzarella - Chávez Miranda, Janira Tatiana (2019)
In this work, fermented mozzarella cheese was elaborated in different percentages (5.10 and 15%) with lactic acid bacteria (Lactococcus spp), originating from the mucilage of fine aroma cocoa, to obtain lactic acid bacteria (BAL). for 48 hours in mucilage, then it was cultivated in bottles of 50, 100 and 150ml, successively it is left to mature for 24 hours at 4 ° C, later to be added in the milk, leaving to rest for 5 minutes and adding the rennet leaving to rest for 25 minutes for the production of mozzarella cheese, a completely randomized statistical design was applied, with four factors and four repetitions, with the percentages of fermentation being the treatments, the Tukey multiple range test was used at 5% probability, with result was obtained mozzarella cheeses corresponding to the percentages of 5, 10, 15%, all treatments were accepted there was no statistical difference. Bromatological analyzes were carried out on mozzarella cheese (ph of cheese, humidity, dry matter, fat, protein, phosphorus, calcium, elasticity), microbiological analyzes to determine the presence of E. Coli, Total Coliforms, Salmonella, Staphylococcus aureus, Mold and Yeasts, organoleptic characteristics (color, smell, taste, acidity, texture, acceptability) were also evaluated. According to the statistical analysis carried out, it was determined that there is no statistical difference between treatments in the bromatological variable of ph of cheese and fat. Unlike moisture, dry matter, protein, phosphorus, calcium and elasticity, there was a significant difference in the treatments. In such a way that the requirements indicated by the NTE INEN 082 were met. It is concluded that treatment 1 (5% fermentation of cocoa mucilage rich in BAL) stood out favorably, in the bromatological characteristics compared to the other treatments, with a Ph of 4.96, humidity or loss due to heating 26.53, dry matter or total solids 73.18, ethereal extractor or crude fat 24.62, total nitrogen or crude protein 32.68, minerals P 142.52 and calcium 2066.06. Similarly in the organoleptic variable it was shown that all treatments were pleasant with a score of 4 points, within the scale of 5. Finally, a mass balance was made and the performance of mozzarella cheese was determined with a 1.075kg.